From fashion to farm: Green marketing innovation strategies in the Brazilian organic cotton ecosystem. (1st August 2022) - Oliveira Duarte, Larissa; Vasques, Rosana Aparecida; Fonseca Filho, Homero; Baruque-Ramos, Julia; Nakano, Davi
Abstract: This study explores how green marketing innovations have been co-created by Brazilian organic cotton ecosystem participants, in order to understand how they develop green marketing innovation strategies together. Organic cotton in Brazil shows how initiatives and programs that act above commercial interests could offer guidance and promote cohesion in the ecosystem. To discuss how collaborative achievements and green marketing strategies can impact innovation, a case study on the Brazilian organic cotton ecosystem was conducted. Results showed that the evolution of organic cotton was based on the initiative of designers and branded producers, and on a network that includes Brazilian R&D institutions, international and Brazilian non-governmental organisations (NGOs), smallholders' associations, and the government. Their joint effort built the ecosystem and led smallholders to adopt sustainable agroecological practices such as rainfed crops, soil nutrition, biodiversity maintenance, and integrated fibre and food crop production. The outcomes of those initiatives are enhanced production, expanding market opportunities, and better social and economic conditions for families in rural areas. For the advance of knowledge about green marketing, this paper offers a perspective that includes a marketing pillar and an ecosystem pillar. Graphical abstract: Image 1 Highlights: Collaboration surrounds various opportunities for green marketing innovations. Organic/agroecological cotton projects allow stakeholders value co-creation. Joint marketing actions include private/public sectors, communities and NGOs. Fashion brands and R&D institutions articulate smallholders and multi-partners. Brazilian organic cotton synergies enhance the ecosystem potential.